Gestión por procesos y los indicadores de cumplimiento en la red de mercados municipales - Rivas Chávez, Edwin Alí (2022)
The present investigative work focuses on denoting the relevance of process management in any existing institution in society, regardless of whether it is public or private, in this case the object of study is the different food markets that make up the network of municipal markets of Guayaquil, Posorja and Tenguel, which are administered by the Very Illustrious Municipality of Guayaquil. Deficiencies in the individual management of the different public servants that make up the market network become bottlenecks that threaten the institutional mission that is based on meeting the basic needs of the canton. The reason for the investigation is to determine a management model by processes that allows verifying compliance with them in the management of municipal markets. The research conducted uses both a qualitative and quantitative approach to data collection and analysis. Finally, the results obtained contribute to a solution proposal based on compliance with the different processes that make up the market network.........